2016
DOI: 10.1016/j.healun.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Lung intragraft donor-specific antibodies as a risk factor for graft loss

Abstract: In lung transplantation, gDSA appears to be a valuable biomarker to identify pathogenic DSA and LTRs with a higher risk for graft loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
40
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 42 publications
3
40
1
Order By: Relevance
“…Multiple individual studies, however, reported a stronger link between CLAD and survival with higher MFI antibodies as well as dnDSA associated with concurrent AMR. 7,11,13,16 Third, both pre-and post-transplant screening intervals showed significant variability. Studies with less frequent pre-transplant screens may have overestimated the incidence of dnDSA since antibodies identified as de novo posttransplant may have been missed pre-transplant because of limited screening and potential sensitization events.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Multiple individual studies, however, reported a stronger link between CLAD and survival with higher MFI antibodies as well as dnDSA associated with concurrent AMR. 7,11,13,16 Third, both pre-and post-transplant screening intervals showed significant variability. Studies with less frequent pre-transplant screens may have overestimated the incidence of dnDSA since antibodies identified as de novo posttransplant may have been missed pre-transplant because of limited screening and potential sensitization events.…”
Section: Discussionmentioning
confidence: 95%
“…Because there was no clear way of aggregating centers by MFI threshold, we could not assess the impact of utilizing higher MFI cut‐offs on the prevalence of dnDSA development or on the correlation between higher MFI and organ and patient survival. Multiple individual studies, however, reported a stronger link between CLAD and survival with higher MFI antibodies as well as dnDSA associated with concurrent AMR …”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Donor and recipient HLA‐typing is also essential in pre‐ and post‐transplant monitoring in order to precisely identify donor‐specific antibodies (DSA). Indeed, preformed and de novo DSA are associated with graft rejection, dysfunction, and loss . The link between DSA and graft outcomes has been particularly emphasized because the development of Single Antigen Flow Beads assays that, for now, allows humoral reactivity against around 200 class‐I and ‐II HLA antigens to be studied.…”
Section: Introductionmentioning
confidence: 99%